An explorative qualitative study on acceptability of physical activity assessment instruments among primary care professionals in southern Sydney. Issue 1 (December 2016) - Dutton, Shona; Dennis, Sarah; Zwar, Nicholas; Harris, Mark
Abstract Background There are a substantial number of instruments for primary-care clinicians to assess physical-activity (PA). However, there are few studies that have explored the views of clinicians regarding comparative acceptability and ease of use. A better understanding of how clinicians perceive instruments could help overcome barriers, and inform future interventions. This study explored the acceptability of five PA-assessment instruments amongst a sample of Australian primary-care clinicians, including family-physicians (FP) and practice-nurses (PN). Methods A purposive sample of FPs (N = 9) and PNs (N = 10) from eight family-practices in southern Sydney consented to participate. Stage-1 involved semi-structured interviews with participants to select preferred instruments. An analysis of the two preferred instruments was conducted as Stage-2, to identify differences in instrument purpose and content. Stage-3 involved participants using the two instruments, selected from Stage-1, for 12-weeks. At the end of this period, semi-structured interviews were repeated to explore clinician experience. Results Clinicians indicated preferences for the GP-Physical-Activity-Questionnaire and 3-Questionnaire Physical-Activity-Questionnaire. These instruments demonstrated distinct variations in content, theoretical orientation, and outcome measures. Reasons for preference included; variations in individual clinician PA levels, knowledge in PA-assessment and instrument features. Conclusion Findings demonstrated two instruments as preferred. Reasons for preference related to internal characteristics of clinicians such as variations in the level of individual PA and external circumstances, such as instrument features.